Characterization of the RNA Mycovirome Associated with Grapevine Fungal Pathogens: Analysis of Mycovirus Distribution and Their Genetic Variability within a Collection of Botryosphaeriaceae Isolates - Gwenaëlle Comont; Chantal Faure; Thierry Candresse; Marie Laurens; Sophie Valière; Jérôme Lluch; Marie Lefebvre; Sébastien Gambier; Jérôme Jolivet; Marie-France Corio-Costet; Armelle Marais (Viruses, 2024)
Botryosphaeriaceae are fungi involved in the decay of various woody species, including the grapevine, leading to significant production losses. This fungal family is largely ubiquitous, and seven species of Botryosphaeriaceae have been identified in French vineyards, with variable levels of aggressiveness, both in vitro and in planta. Mycoviruses can impact the life traits of their fungal hosts, including aggressiveness, and are one of the factors influencing fungal pathogenicity. In this study, the RNA mycovirome of fifteen Botryosphaeriaceae isolates was characterized through the high-throughput sequencing of double-stranded RNA preparations from the respective samples. Eight mycoviruses were detected, including three potential novel species in the Narnaviridae family, as well as in the proposed Mycobunyaviridae and Fusagraviridae families. A large collection of Botryosphaeriaceae isolates was screened using RT-PCR assays specific for 20 Botryosphaeriaceae-infecting mycoviruses. Among the mycoviruses detected, some appeared to be specialists within a single host species, while others infected isolates belonging to multiple Botryosphaeriaceae species. This screening allowed us to conclude that one-third of the Botryosphaeriaceae isolates were infected by at least one mycovirus, and a significant proportion of isolates (43.5%) were found to be coinfected by several viruses, with very complex RNA mycoviromes for some N. parvum isolates.